We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
322
1
avatar

If h(x) = (−x + 1)2 − 5 and g(x) = −x − 2 , then (h ◦ g)(x) =?

 Oct 29, 2017
 #1
avatar+100809 
+2

If h(x) = (−x + 1)2 − 5 and g(x) = −x − 2 , then (h ◦ g)(x) =?

h(x) = (−x + 1)2 − 5 = -2x+2-5 = -2x-3

 

(h ◦ g)(x) = -2[−x − 2] - 3 

(h ◦ g)(x) = [2x + 4] - 3 

(h ◦ g)(x) = 2x + 1


 

 Oct 29, 2017

21 Online Users

avatar